Penerapan Metode Waterfall dalam Pengembangan Aplikasi Schedule Maintenance Alat Produksi - Mailasari, Mely; Winnarto, Monikka Nur; Purnamawati, Annida (Infotek: Jurnal Informatika dan Teknologi, 2024)
PT. Shiroki Indonesia Cikarang is moving on the field of automotive spare parts manufacturing such as window regulator, seat recliner, sear track as well as floor lock. The activity uses a tool/machine as a support to produce spare parts that have good quality. With so many of these machines, then the company needs to do the maintenance and also the maintenance of the machine well. Scheduling of maintenance and maintenance of machinery production equipment still uses the record on board and requires information from the operator to be submitted to the technician. Therefore, it is necessary to create a web-based maintenance schedule application that can facilitate the performance of the staff in making the maintenance schedule of the production equipment more effective and efficient as well as the availability of reports from the maitenance. The research method used is the waterfall method which has five stages namely needs analysis, design, program code making, testing and support or maintenance. The schedule maintenance application was created using the PHP programming language using the CodeIgniter framework and the MySql database.